Sources of organizational stress among athletes in the Malaysian public universities / Wee Eng Hoe … [et al.] - Wee, Eng Hoe; Kee, Kang Mea; Ong, Tah Fatt; Tan Abdullah, Nadiah Diyana (2009)
This study is to assess organizational stress among athletes in the Malaysian Public Universities. Specifically, it is to assess organizational stress among athletes competing in sports programmes (Intra-varsity sports programme, Inter-varsity sports competition, Interstates sports competition & International sports competition). The Organizational Stress Inventory (OSI) questionnaire was adopted and adapted from research done by Fletcher and Hanton (2003). The inventory is divided into three categories: personal issues (16 statements), leadership issues (21 statements), and environmental issues (45 statements). A total of 273 student athletes were surveyed. The findings are as follows: a) The three sub-domains were ranked first (personal issues), second (environmental issues) and third (leadership issues) for the respondents of the whole sample, males and females respondents. b) The unweighted mean scores showed that organizational stress were dominant for 'Personal Issues' and 'Environmental Issues' for all the respondents. c) For the 'Personal Issue' domain, the sub-domains of 'nutrition', 'injury' and 'goal & expectation' were ranked in order of importance respectively. Similar ranking applied to both male and female athletes. Similar ranking applied individually to male and female athletes. d) For the 'Leadership Issues', 'Coaching Styles' was ranked first, followed by 'Coach' subdomain. However, both the sub-domains were not dominant. e) For the 'Environmental Issues' the first three main sub-domains were 'finances', 'selection' and accommodation during competition'. f) For male athletes (N=160), the three sub-domains were ranked first (personal issues), second (environmental issues) and third (leadership issues). g) For female athletes (N=113), the three sub-domains were ranked first (personal issues), second (environmental issues) and third (leadership issues). h) There was no significant difference in organizational stress among athletes according to gender, i) There was no significant difference in organizational stress among athletes according to age groups. However, there was statistically significant difference in 'goal & expectation' sub-domain based on age groups, j) There was no significant difference in organizational stress among athletes according to category of sports, k) There was no significant difference in organizational stress among athletes according to level of involvement. 1) There was significant difference in 'finances' sub-domain of the 'Environmental Issues'. Zone level athletes (mean=20.10) were more stressed as compared to college level athletes (mean=13.69). The findings have significant implications for coaches and sport programme directors. Based on the findings of this study, additional research is needed and the following suggestions are considered important. Since the sample of this study is confined to public university athletes, similar study should be conducted on other groups of student from private educational institutions. As only about 5.5% of national athletes were involved in this study, a follow-up study is recommended to concentrate on national athletes and to compare stress among other national teams.